A Software Maintainability Attributes Model - Hashim, Khairuddin (Malaysian Journal of Computer Science, 1996)
Examines the factors that affect the maintainability of a software. The proposed model can be used to highlight the need to improve the quality of the product so that proper and efficient maintenance is feasible without much difficulty. It can also be used to develop a measurement for maintainability which can be used to measure the level of maintenance readiness before the completion and delivery of a software product.